1994
DOI: 10.1007/bf00195512
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter embolization of the marginal artery of drummond as treatment for life-threatening retroperitoneal hemorrhage complicating heparin therapy

Abstract: We report a case in which life-threatening retroperitoneal hemorrhage complicated heparin therapy. The bleeding originated from the marginal artery of Drummond which was catheterized with a 3-Fr coaxial catheter system (Tracker-18 catheter) and embolized with microcoils. Bleeding stopped and no ischemic complications developed for 3 years after embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The classic view that anticoagulation-related soft-tissue bleeding was an angiographically occult diffuse microvascular condition, in which catheter angiography had no diagnostic or therapeutic role, has been challenged by several case reports [5,6,[9][10][11][12][13][14][15][16][17][18][19][20]. In our daily clinical experience with this specific clinical situation, we have noticed that the visualization of active bleeding on MDCTA calls for more urgent management [18,23,[32][33][34][35].…”
Section: Embolization For Soft-tissue Hemorrhagementioning
confidence: 99%
“…The classic view that anticoagulation-related soft-tissue bleeding was an angiographically occult diffuse microvascular condition, in which catheter angiography had no diagnostic or therapeutic role, has been challenged by several case reports [5,6,[9][10][11][12][13][14][15][16][17][18][19][20]. In our daily clinical experience with this specific clinical situation, we have noticed that the visualization of active bleeding on MDCTA calls for more urgent management [18,23,[32][33][34][35].…”
Section: Embolization For Soft-tissue Hemorrhagementioning
confidence: 99%
“…There is no prior report of hemorrhage in the gluteal region. Usually hemorrhagic complications in patients receiving anticoagulant therapy result from small artery rupture [9]. In our patient, the proximal portion of the superior gluteal artery had ruptured and a large pseudoaneurysm formed, extending from the pelvic cavity to the gluteal region through the greater ischiatic foramen.…”
Section: Discussionmentioning
confidence: 89%
“…When spontaneous retroperitoneal hemorrhage occurs, signs and symptoms may be ambiguous and diagnosis may be delayed [2]. There are reports of approximately 30 cases of spontaneous retroperitoneal hemorrhage during oral anticoagulant therapy [2][3][4]9]. There is no prior report of hemorrhage in the gluteal region.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Surgical intervention has been considered the only option for uncontrollable hemodynamic collapse. Reports of transcatheter arterial embolization in anticoagulant-related RPH are very scarce, and a review of the literature revealed very few reports of successful cases [8,9]. But Zissin et al [10] reported that this therapeutic option seemed relevant in anticoagulated patients with large soft tissue hematomas that typically occur spontaneously and are difficult to either predict or prevent.…”
Section: Discussionmentioning
confidence: 99%